Implementasi Kurikulum Outcome Based Education pada Pembelajaran Bahasa Arab di Perguruan Tinggi Keagamaan Islam Negeri - Luthfi Abdul Manaf; Hamida Gadoum; Asmaul Husna; Inchinia Angger Rowin; Ahmad Arif Musyafa' (Al Maghazi : Arabic Language in Higher Education, 2026)
The Outcome Based Education (OBE) approach has a principle that focuses on the final results or achievements that must be mastered by students so as to support the Independent Learning and Independent Campus program, but there are still few researchers who discuss this approach at the tertiary level, especially in Arabic language learning. The purpose of this study is to determine the Implications, Impacts, and Optimization of the Outcome Based Education (OBE) Curriculum in Arabic language learning at UIN Maulana Malik Ibrahim Malang. In this study, the researcher used a Qualitative approach with a descriptive analysis type, while the type of research is a Case Study with the aim of obtaining comprehensive and systematic information about the implementation of Outcome-Based Education in Arabic language courses for UIN Maulana Malik Ibrahim Malang students. Several methods used by researchers to obtain research data are the Participant Observation Method, In-depth Interviews, and Documentation. While the Data Analysis Technique uses Miles and Huberman's Theory. The result of the research is that the concept of the Outcome-Based Education Curriculum in Arabic Language Learning at UIN Maulana Malik Ibrahim Malang is specifically managed by the Language Development Center through synergy with the faculty to determine the Learning Outcome Design for Arabic Language Course Graduates, which encompasses aspects of Basic Arabic, Structure and Vocabulary, and Communicative and Practical Arabic. These four outcomes are integrated into comprehensive Arabic Language Competence, which is developed through the development of Semester Learning Plans (RPS) as a reference in the learning process. The impacts of the OBE Curriculum implementation include aligning learning outcomes with the graduate profiles of each study program, necessitating the development of PKPBA Academic Guidelines for each class. Furthermore, teaching resources are mapped according to the needs of the Faculty and the classification of student abilities, which are divided into three classes: Tamhidi, Mubtadi', and Fash al-jami'. Optimization is achieved by providing flexibility for lecturers to innovate methods and strategies in accordance with the principles of the OBE Curriculum. In addition, UIN Maulana Malik Ibrahim provides facilities, both infrastructure and workshops, to improve the competence of Arabic language lecturers.